Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Solusi Indosistem Otomat - Salsabilla, Elsa; Aprillia, Frida; Fransisco Siboro, Sonny (CV Warnak Johanna Nusantara, 2026)
This study was conducted to analyze the influence of organizational culture and work discipline on employee performance at PT Solusi Indosistem Otomat which operates in the field of Industrial Automation and Power Transmission and Distribution. The objectives of this study are 1. To determine the influence of organizational culture on employee performance partially, 2. To determine the influence of work discipline on employee performance partially, and 3. To determine the influence of organizational culture and work discipline simultaneously on employee performance. on employees of PT Solusi Indosistem Otomat. The sample used in this study was 50 employees. The data analysis technique used the SPPS Version 27 application. The results of this study were obtained using the t test that organizational culture partially had a significant effect on employee performance with a significant value of 0.000 <0.05 and the results of the t test were t count 8,742 > t table 2,011. Work discipline partially had an effect on employee performance t count 9,585> t table 2,011 Organizational culture and work discipline simultaneously have a significant effect on employee performance, with a significance value of 0,000 < 0,05 and an F-test result of 67,520 > 3,19